Handover training for medical students: a controlled educational trial of a pilot curriculum in Germany. Issue 9 (12th September 2018) - Thaeter, Laura; Schröder, Hanna; Henze, Lina; Butte, Jennifer; Henn, Patrick; Rossaint, Rolf; Sopka, Saša
Abstract : Objective: The aim of this study was to implement and evaluate a newly developed standardised handover curriculum for medical students. We sought to assess its effect on students' awareness, confidence and knowledge regarding handover. Design: A controlled educational research study. Setting: The pilot handover training curriculum was integrated into a curriculum led by the Departments of Anesthesiology and Intensive Care (AI) at the University Hospital. It consisted of three modules integrated into a 4-week course of AI. Multiple types of handover settings namely end-of-shift, operating room/postanaesthesia recovery unit, intensive care unit, telephone and discharge were addressed. Participants: A total of n=147 fourth-year medical students participated in this study, who received either the current standard existing curriculum (no teaching of handover, n=78) or the curriculum that incorporated the pilot handover training (n=69). Outcome measures: Paper-based questionnaires regarding attitude, confidence and knowledge towards handover and patient safety were used for pre-assessment and post-assessment. Results: Students showed a significant increase in knowledge (p<0.01) and self-confidence for the use of standardised handover tools (p<0.01) as well as accurate handover performance (p<0.01) among the pilot group. Conclusion: We implemented and evaluated a pilot curriculum for undergraduate handover training. Students displayed a significant increase in knowledge and self-confidence for the use of standardised handover tools and accuracy in handover performance. Further studies should evaluate whether the observed effect is sustained across time and is associated with patient benefit.